Segregation of minichromosomes in trypanosomes: implications for mitotic mechanisms. - Gull, K; Alsford, S; Ersfeld, K (1998)
In addition to 11 pairs of housekeeping chromosomes, the genome of Trypanosoma brucei contains approximately 100 minichromosomes that are probably involved in the ability of the parasite to evade the host's immune response. This minichromosomal population is segregated on the mitotic spindle. How this is achieved provides insight into potential segregation mechanisms for small DNA molecules in eukaryotic microorganisms.